How Do Cooperatives Alleviate Poverty of Farmers? Evidence from Rural China - Yun Shen; Jinmin Wang; Luyao Wang; Bin Wu; Xuelan Ye; Yang Han; Rui Wang; Abbas Ali Chandio (Land, 2022)
Farmers’ cooperatives play an important role in enabling small farmers to integrate into modern agriculture. Based on the survey data of 7200 farmers in four provinces of China, this paper uses the multi-dimensional poverty measurement method and the instrumental variable method to reveal the transmission mechanism and multi-dimensional poverty reduction effect of farmers’ cooperatives in deep poverty-stricken areas in China to realize joint agricultural empowerment through the supply chain. The results show that farmers’ cooperatives play an important role in enhancing small farmers’ financing, technology application, market sales, and rights decision-making. Every increase in the degree of interest connection between the two will help farmers reduce the multi-dimensional poverty level by 12.3%, and the mitigation effects on material poverty, ability poverty, and rights poverty are between 10% and 13%. Compared with agricultural cooperatives with weak organizational service capacity, cooperatives with high organizational service capacity have a more significant multi-dimensional poverty reduction effect on farmers, which leads to farmers obtaining financing and improving their ability and income. In addition, the difference in benefit coupling between agricultural cooperatives and farmers of different leading bodies also results in the heterogeneity of multi-dimensional poverty alleviation effects of farmers. To a certain extent, the supply chain is affected by the risk endowment of members, the supply chain’s poverty alleviation performance is affected by members’ supply chain’s poverty alleviation performance, and there is a certain risk transfer and “distribution failure”. Therefore, optimizing the benefit coupling structure and risk sharing mechanism between farmers’ cooperatives and farmers has become an important way to break the pattern of “the strong are always strong” and “distribution failure” for supply chain members and farmers.